Application of Statistical Process Control at Food Joint: A Case Study of Inasis SME Café - Lai, Jian Wei; Taib, Che Azlan (Universiti Utara Malaysia, 2019)
This research investigates the statistical process control (SPC) as an improvement tool in one of the Café UUM. This research is using SPC tool to identify the waiting time of student who order their food at SME Cafe. In this research there are three objectives to cover, which is to determine the waiting time of student to get their food, to calculate the upper and lower control limit and to calculate the process capability of Inasis SME Café. This research collects 500 set of data from the sample of the entire population students who take their dinner in SME Cafe, UUM. The data analysis technique used for this research is the x̅ and R chart. The findings will be presented in relation to the research objectives stated in this research. Results are presented in respect of the waiting time of student to get their food in SME Café. The results of this research will be indicated duration of time to prepare food based on the rule of control chart